The response of Monoterpenes to Different Enzyme Preparations in Gewürztraminer (Vitis vinifera L.) Wines - Rusjan, D.; Strlič, M. Strlič; KoÅ¡merl, T.; Prosen, H. (South African Journal of Enology and Viticulture, 2016)
The α-terpineol, linalool, nerol and geraniol, which are the main aromatic monoterpenes in the grapevine variety Gewürztraminer, were determined in the grapes, must and wine after treatment with six different pectolytic enzymes [Lallzyme-β (‘Lall’); Rohavin VR-C (‘VRX’), Rohapect D5L (‘D5L’), Rohavin MX (‘MX’), Rohapect VRC (‘VRC’), Endozym cultivar A (‘Cult. A’)], and after treatment with β-glucosidase (βG, EC 3.2.1.21). The concentrations of monoterpenic compounds were determined by solid-phase microextraction (SPME) and GC-MS. The most abundant monoterpene in the grapes of Gewürztraminer was geraniol (66.7 μg/L), followed by nerol (13.3 μg/L), α-terpineol (7.8 μg/L) and finally linalool (3.3 μg/L). Gewürztraminer wine from must treated with the Lall enzyme preparation was the most aromatic, which was also confirmed by chemical and sensory analysis in which the concentrations of nerol (45.9 μg/L), geraniol (31.8 μg/L), α-terpineol (10.5 μg/L) and linalool (6.1 μg/L) were determined. The wines produced from must treated chemically with enzymes showed higher concentrations of many of the monoterpene compounds compared to the control, although the sensorial analysis did not affirm this convincingly.